AN ANALYSIS OF THE EFFECT TEACHING STRATEGIES USING FILM OR VIDEO FOR SPEAKING AND LISTENING - Tria Adinda Rustandi; Syafrizal (STKIP Subang, 2024)
This article is aim to analysis some part of theories and previous study about the analysis of the effect teaching strategies using film or video to improve student motivation in studying English in speaking and listening. In the last decade, learning English is important part of for we to communicate and collaborate in many aspect including politic, economic, social, and education with others people around the world. However, Indonesian Student that has young learner they often lack of Interest to learning this language. The main reason to the lack of students motivation are the teaching method that tend to be boring and teachers centered. Therefore, one of the alternative solutions to answer this problem are implementing of watching film or video in classroom. One of the simplest way to using film and videos are watching music and watching music video with groups of students. The teacher will show some films and videos and see how they would enthusiasm using this method. This also will enrich the student speaking and listening along film or videos was played on. Hence, this paper will describe theory of the affect using film or videos, with using quantitative descriptive as a methods for this research and see the advantage of using film or videos and how to imply that film or videos using in English classroom